2001
DOI: 10.1093/humrep/16.9.1954
|View full text |Cite
|
Sign up to set email alerts
|

Developmental ability of chromosomally abnormal human embryos to develop to the blastocyst stage

Abstract: Even though there is a strong selection against chromosomally abnormal embryos, extended culture to day 5 or 6 cannot be used as a reliable tool to select against clinically relevant chromosome abnormalities such as trisomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
138
4
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(165 citation statements)
references
References 32 publications
15
138
4
7
Order By: Relevance
“…Some IVF centers even limited the last age for IVF as 43 years old [8]. Women with advanced maternal age will have poor ovary response during controlled ovary hyperstimulation (COH), low retrieved oocyte number, lowoocyte fertilization rate, low good quality embryo rate, low embryo implantation rate, low pregancy rate, high miscarriage rate, high preterm delivery rate and high birth defect rate [6,[9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Some IVF centers even limited the last age for IVF as 43 years old [8]. Women with advanced maternal age will have poor ovary response during controlled ovary hyperstimulation (COH), low retrieved oocyte number, lowoocyte fertilization rate, low good quality embryo rate, low embryo implantation rate, low pregancy rate, high miscarriage rate, high preterm delivery rate and high birth defect rate [6,[9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…
We used fluorescent in situ hybridisation (FISH) to detect nine chromosomes (1,13,15,16,17,18,21,22 and X) in 89 first Polar Bodies (1PBs), from in vitro matured oocytes discarded from IVF cycles. In 54 1PBs, we also analysed the corresponding oocyte in metaphase II (MII) to confirm the results; the other 35 1PBs were analysed alone as when preimplantation genetic diagnosis using 1PB (PGD-1PB) is performed.
…”
mentioning
confidence: 99%
“…While this may in part be due to the fact that the one blastomere biopsy group had a significantly higher number of embryos biopsied per PGD cycle, it is also possible that the one blastomere biopsy group contained embryos which would have been identified as mosaic unbalanced if two blastomeres had been biopsied. Sandalinas et al [11] and Emiliani et al [5] reported that mosaic embryos are capable of developing to the blastocyst stage. Based on this, it could be hypothesised that a mosaic unbalanced embryo incorrectly diagnosed as "normal/balanced" following one blastomere biopsy has the potential to reach the blastocyst stage and be transferred.…”
Section: Discussionmentioning
confidence: 99%